Improving Students’ Speaking Skill In English Lesson With Action Learning Strategy - Zainuddin (Yayasan Insan Cipta Medan, 2023)
This research aimed to improved the students’ speaking skill in English lesson by using action learning strategy. This research was conducted by using Classroom Action Research (CAR). The subject of this research was X grade of MAN 1 Padangsidimpuan which consisted of 48 students. The objective of this research was to improve students’ speaking skill in English Lesson by using Action Learning strategy at Eight Grade of MAN 1 Padangsidimpuan. This research was conducted in two cycles which each consists’ of planning, acting, observing, and reflecting. The data were gathered through quantitative and qualitative data. The result of this reserach showed that there was increasing of students in speaking skill. The mean of pre-test was 59. The mean of post-test 1 was 75.04. the mean of post-test 2 was 82.11. It indicated that the scores and the mean in second cycle were better than the first cycle. The percentage of students who got point >75 also grew up. In the pre-Test, the students who got point >75 up were 4 students (9.09%). In the post-test of cycle 1 students who got point >70 up were 30 students (68.18%). The post-test of cycle 2, students who got point >75 were 38 students (86.36%). In other words, the students’ ability in speaking improved and became well in the first meeting to the next meeting.